Association of HbA1c/HDL-C ratio and depression with cardiometabolic multimorbidity in middle-aged and older adults: a nationwide prospective cohort study - Dong, Jiayang; Huang, Aodi; Zhang, Zhiqiang; Yang, Xinyue; Sun, Jiayi; Zhang, Wenjuan (Frontiers in Nutrition, 2025)
BackgroundCardiometabolic multimorbidity (CMM)—the coexistence of two or more cardiometabolic diseases such as diabetes, heart disease, and stroke—poses serious health risks. Depression has recently been recognized as an independent risk factor for CMM. However, the role of the glycosylated hemoglobin A1c to high-density lipoprotein cholesterol ratio (HbA1c/HDL-C) in predicting CMM remains unclear. This study investigates the independent and combined effects of the HbA1c/HDL-C ratio and depression on CMM risk in middle-aged and older adults.MethodsData were drawn from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2018, including 7,256 participants aged 45 and above. Kaplan–Meier analysis estimated cumulative CMM incidence. Multivariable Cox proportional hazards models assessed the independent and joint effects of the HbA1c/HDL-C ratio and depression on CMM risk. Restricted cubic splines evaluated potential nonlinear relationships. Receiver operating characteristic (ROC) analysis compared the predictive performance of the HbA1c/HDL-C ratio, depression, and their combination. Subgroup and sensitivity analyses tested the robustness of findings.ResultsOver the 7-year follow-up, 419 participants (5.77%) developed CMM. Higher HbA1c/HDL-C ratios and depression were associated with greater cumulative incidence of CMM. The HbA1c/HDL-C ratio was positively associated with CMM risk, showing a nonlinear trend. Participants with both a high HbA1c/HDL-C ratio and depression had significantly increased CMM risk (HR = 2.59, 95% CI: 1.82–3.68) compared to those with either factor alone. Combined analysis consistently outperformed single predictors in ROC analysis. Subgroup and sensitivity analyses confirmed the robustness of results. Depression did not mediate the HbA1c/HDL-C–CMM association.ConclusionBoth the HbA1c/HDL-C ratio and depression are independently associated with CMM. Depression did not mediate the association between the HbA1c/HDL-C ratio and CMM. Their combined effect substantially increases CMM risk, underscoring the importance of integrating metabolic and psychological assessments in early identification and personalized prevention strategies for high-risk populations.